Оцінки білінійних наближень класів SΩp,θB періодичних функцій двох змінних - Соліч, К.В. (Український математичний журнал, 2012)
Получены точные по порядку оценки наилучших билинейных приближений классов SΩp,θB периодических функций двух переменных в пространстве Lq для некоторых соотношений между параметрами p,q,θ. We obtain exact-order estimates for the best bilinear approximations of the classes SΩp,θB of periodic functions of two variables in the space L q for some relations between the parameters p, q, and θ.